The education of children in care: Agency and resilience. (June 2017) - Berridge, David
Abstract: This paper considers the educational experiences and progress of children in care in England. As part of a mixed methods study 26 young people, together with their carers, social workers and teachers, were asked about their educational experiences and the contributory factors to educational progress during secondary schooling. Responses from young people revealed that they were exercising control over their educational experiences – an expression of agency . They chose to engage with learning once they felt the problems in their lives were being managed and, therefore, that certain preconditions were being met. Analysis of this qualitative data was set within a theoretical framework linking the Sociology of Childhood with the Social Ecology of Resilience. Four groups of young people were identified who demonstrated different responses: ' Stressed / unresolved '; ' Committee / trusted support '; ' Private / self-reliant '; and ' Disengaged '. The implications are discussed for social workers and schools in working with young people to improve their educational progress and attainment. Highlights: Children in care were exercising control over their educational experiences. Children's expression of agency was linked with the social ecology of resilience. Young people felt overwhelmingly that entry to care had improved their lives. A fourfold typology differentiated children's attitudes to learning. Stable, fulfilling relationships enabled children to engage more with learning.